Development and psychometric validation of a brief comprehensive health status assessment scale in older patients with hematological malignancies: The GAH Scale. Issue 5 (September 2015) - Bonanad, S.; De la Rubia, J.; Gironella, M.; Pérez Persona, E.; González, B.; Fernández Lago, C.; Arnan, M.; Zudaire, M.; Hernández Rivas, J.A.; Soler, A.; Marrero, C.; Olivier, C.; et al.
Abstract: Objectives: The purpose of this study was to develop a new brief, comprehensive geriatric assessment scale for older patients diagnosed with different hematological malignancies, the Geriatric Assessment in Hematology (GAH scale), and to determine its psychometric properties. Materials and Methods: The 30-item GAH scale was designed through a multi-step process to cover 8 relevant dimensions. This is an observational study conducted in 363 patients aged ≥ 65 years, newly diagnosed with different hematological malignancies (myelodysplasic syndrome/acute myeloblastic leukemia, multiple myeloma, or chronic lymphocytic leukemia), and treatment-naïve. The scale psychometric validation process included the analyses of feasibility, floor and ceiling effect, validity and reliability criteria. Results: Mean time taken to complete the GAH scale was 11.9 ± 4.7 min that improved through a learning-curve effect. Almost 90% of patients completed all items, and no floor or ceiling effects were identified. Criterion validity was supported by reasonable correlations between the GAH scale dimensions and three contrast variables (global health visual analogue scale, ECOG and Karnofsky), except for comorbidities. Factor analysis (supported by the scree plot) revealed nine factors that explained almost 60% of the total variance. Moderate internal consistency reliability was found (Cronbach's α: 0.610), and test–retest was excellent (ICC coefficients, 0.695–0.928). Conclusion: Our study suggests that the GAH scale is a valid, internally reliable and a consistent tool to assess health status in older patients with different hematological malignancies. Future large studies should confirm whether the GAH scale may be a tool to improve clinical decision-making in older patients with hematological malignancies.